PENGEMBANGAN JOB SHEET TELEPON OPERATOR BERBASIS COMPETENCY BASED TRAINING DI FRONT OFFICE DEPARTMENT - Dhera Shaumy Oshita, - (2020)
Latar belakang penelitian ini yaitu peserta didik belum memahami job sebagai Telepon Operator secara maksimal sesuai standar operasional dan hanya terdapat satu job sheet saja. Penelitian bertujuan untuk mengembangkan job sheet Telepon Operator berbasis competency based training di Front Office Department. Metode penelitian yang digunakan yaitu research and development (R&D) dengan model PPE yang dikembangkan oleh Richey and Klein. Instrumen penelitian yang digunakan untuk penelitian terdiri dari wawancara, studi dokumentasi dan format validasi. Expert judgment dilakukan oleh dua ahli kurikulum dan pembelajaran serta dua ahli materi Akomodasi Perhotelan. Hasil penelitian menunjukkan bahwa hasil expert judgment ahli kurikulum dan pembelajaran yang mencakup judul, kompetensi dasar, indikator, peraturan kegiatan praktik, tahapan praktik, dan panduan self evaluation mencapai nilai rata-rata 91,67% dengan kriteria sangat layak. Hasil dari ahli materi Akomodasi Perhotelan yang meliputi tahapan persiapan, tahap prosedur praktik Telepon Operator dan Tahap hasil praktik, menunjukkan hasil 99,17% dengan kriteria sangat layak. Kesimpulannya bahwa job sheet Telepon Operator berbasis competency based training di Front Office Department termasuk kriteria sangat layak digunakan dengan nilai rata-rata 94,19%. The background of this research is because the learners havn't yet understood the job as the Phone Operator according to the standard operational procedure, moreover there was learners who must did remedial after practice, even though it has been given a Job Sheet by their teacher. The aims of this research is to develop a Phone Operator's Job Sheet based on Competency Based Training at the Front Office Department. The research method which used in this research is Research and Development (R&D) with Planning, Production, Evaluation (PPE) model developed by Richey and Klein. The research instruments for this research consist of interviews, documentation studies and validation formats. Expert judgment is performed by two curriculum and learning experts and two specialist of Hospitality Accommodation. The results showed that curriculum and learning expert's judgement results: titles, basic competencies, indicators, rules of practice activities, stages of practice, and self-evaluation guidelines reached an average value of 91.67% with very decent criteria. The specialists of Hospitality Accommodation's results: preparatory stages, the stage of the Phone Operator practice procedure, and the stage of practice results, shows the results of 99.17% with very decent criteria. The conclusion that Phone Operator's Job Sheets based on Competency Based Training in Front Office Department is well worth to use with an average value of 94.19%.